2023
DOI: 10.1080/10643389.2022.2164154
|View full text |Cite
|
Sign up to set email alerts
|

Metals in coastal seagrass habitats: A systematic quantitative literature review

Abstract: Trace metals in bivalves and seagrass collected from Venezuelan coastal sites. Revista de Biologia Tropical, 56, 215-222. https://www.scopus.com/inward/record.uri?eid=2-s2.0-81855213332&partnerID=40&md5=f192bf3dc92677f4d9563cf8b6abb706 4. Aljahdali, M. O., & Alhassan, A. B. (2020). Heavy metal accumulation and antioxidative feedback as a biomarker in Seagrass Cymodocea Serrulata. Sustainability (Switzerland), 12(7), 2841.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 150 publications
0
0
0
Order By: Relevance
“…The sediment of seagrass ecosystems acts as sink of anthropogenic trace metals (Lee et al, 2023;Mishra et al, 2022;Mishra & Farooq, 2022b). The sediment trace metal concentrations range observed in this study were lower than trace metals concentration range observed for seagrass ecosystems across the coast of India, except for Mg in the sediment of T. hemprichii meadows of Burmanallah, ANI (Table 3).…”
Section: Species-specific Accumulationcontrasting
confidence: 54%
See 3 more Smart Citations
“…The sediment of seagrass ecosystems acts as sink of anthropogenic trace metals (Lee et al, 2023;Mishra et al, 2022;Mishra & Farooq, 2022b). The sediment trace metal concentrations range observed in this study were lower than trace metals concentration range observed for seagrass ecosystems across the coast of India, except for Mg in the sediment of T. hemprichii meadows of Burmanallah, ANI (Table 3).…”
Section: Species-specific Accumulationcontrasting
confidence: 54%
“…Seagrass ecosystems that inhabit the intertidal areas interacts with these anthropogenic contaminants and can be utilized as suitable bioindicators of these trace metals accumulation. However, till date their utilization for monitoring of trace metal contamination in coastal ecosystems has been limited (Govers et al, 2014;H. Lee et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic quantitative review follows a 15-step process that has been used across a wide range of disciplines (Cooper et al, 2023;Guitart et al, 2012;Kim & Cuskelly, 2017;Laird-Gentle et al, 2023;Lee et al, 2022;Mahmoudi et al, 2019;Martellotta et al, 2022;Najafi et al, 2022;Parker & de Baro, 2019;Roy et al, 2012;Steven et al, 2011;Takata & Hallmann, 2021;Thomson et al, 2019). This methodology is characterised as being structured, explicit, quantitative, rigorous, comprehensive and reproducible (Pickering et al, 2021;.…”
Section: Methodsmentioning
confidence: 99%